After Zigzagging Between Extremes, Finally Common Sense? Will Belgium Return to Reasonable Rules on Illegally Obtained Evidence? - Frank Verbruggen; Charlotte Conings (Revista Brasileira de Direito Processual Penal, 2021)
In the absence of statutory rules on the matter, Belgian courts traditionally applied a strict exclusionary rule for illegally gathered evidence and its fruits. The Court of Cassation in 2003 made a spectacular U-turn and prohibited exclusion of illegally obtained evidence by criminal courts, with only very limited exceptions. Parliament subsequently incorporated these judge-made principles into a binding statutory rule. As a new Code is about to be debated in Parliament, the time is right to question the “normalisation” of law enforcement officers’ disrespect for the rules. The Rule of Law will be restored by making exclusion of illegally gathered evidence the rule, but exceptionally allowing its use upon consideration of the conflicting interests.